Surveillance for Hospitalized Acute Respiratory Infection in Guatemala - Verani, Jennifer R.; McCracken, John; Arvelo, Wences; Estevez, Alejandra; Lopez, Maria Renee; Reyes, Lissette; Moir, Juan Carlos; Bernart, Chris; Moscoso, Fabiola; Gray, Jennifer; Olsen, Sonja J.; Lindblade, Kim A. (PloS one, 2013)
Acute respiratory infections (ARI) are an important cause of illness and death worldwide, yet data on the etiology of ARI and the population-level burden in developing countries are limited. Surveillance for ARI was conducted at two hospitals in Guatemala. Patients admitted with at least one sign of acute infection and one sign or symptom of respiratory illness met the criteria for a case of hospitalized ARI. Nasopharyngeal/oropharyngeal swabs were collected and tested by polymerase chain reaction for adenovirus, parainfluenza virus types 1,2 and 3, respiratory syncytial virus, influenza A and B viruses, human metapneumovirus, Chlamydia pneumioniae, and Mycoplasma pneumoniae. Urine specimens were tested for Streptococcus pneumoniae antigen. Blood culture and chest radiograph were done at the discretion of the treating physician. Between November 2007 and December 2011, 3,964 case-patients were enrolled. While cases occurred among all age groups, 2,396 (60.4%) cases occurred in children <5 years old and 463 (11.7%) among adults ≥65 years old. Viruses were found in 52.6% of all case-patients and 71.8% of those aged <1 year old; the most frequently detected was respiratory syncytial virus, affecting 26.4% of case-patients. Urine antigen testing for Streptococcus pneumoniae performed for case-patients ≥15 years old was positive in 15.1% of those tested. Among 2,364 (59.6%) of case-patients with a radiograph, 907 (40.0%) had findings suggestive of bacterial pneumonia. Overall, 230 (5.9%) case-patients died during the hospitalization. Using population denominators, the observed hospitalized ARI incidence was 128 cases per 100,000, with the highest rates seen among children <1 year old (1,703 per 100,000), followed by adults ≥65 years old (292 per 100,000). These data, which demonstrate a substantial burden of hospitalized ARI in Guatemala due to a variety of pathogens, can help guide public health policies aimed at reducing the burden of illness and death due to respiratory infections.